2006
DOI: 10.1073/pnas.0607133103
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy target esterase catalyzes osmoprotective renal synthesis of glycerophosphocholine in response to high NaCl

Abstract: Glycerophosphocholine (GPC) is an osmoprotective compatible and counteracting organic osmolyte that accumulates in renal inner medullary cells in response to high NaCl and urea. We previously found that high NaCl increases GPC in renal [Madin-Darby canine kidney (MDCK)] cells. The GPC is derived from phosphatidylcholine, catalyzed by a phospholipase that was not identified at that time. Neuropathy target esterase (NTE) was recently shown to be a phospholipase B that catalyzes production of GPC from phosphatidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…In contrast, an intriguing feature of mammalian GPPDEs is that these enzymes show restricted substrate specificities, strongly suggesting the physiological roles of mammalian GP-PDEs as a determinant for GroPIns or GroPCho levels in mammalian cells. GroPIns has been shown to be involved in the control of cell proliferation, cell chemotaxis, and cell morphology, affecting in the last case actin cytoskeletal rearrangements through the activation of small GTPases of the Rho family (9,34,35), whereas GroPCho is reportedly an osmoprotective compatible and counteracting organic osmolyte that accumulates in renal inner medullary cells in response to high NaCl and urea (8,36,37). A recent study suggests that GDE2 contributes to osmotic regulation as a GroPCho phosphodiesterase (38).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an intriguing feature of mammalian GPPDEs is that these enzymes show restricted substrate specificities, strongly suggesting the physiological roles of mammalian GP-PDEs as a determinant for GroPIns or GroPCho levels in mammalian cells. GroPIns has been shown to be involved in the control of cell proliferation, cell chemotaxis, and cell morphology, affecting in the last case actin cytoskeletal rearrangements through the activation of small GTPases of the Rho family (9,34,35), whereas GroPCho is reportedly an osmoprotective compatible and counteracting organic osmolyte that accumulates in renal inner medullary cells in response to high NaCl and urea (8,36,37). A recent study suggests that GDE2 contributes to osmotic regulation as a GroPCho phosphodiesterase (38).…”
Section: Discussionmentioning
confidence: 99%
“…SWS mutant flies show spongiform lesions within the CNS, glial hyperwrapping around neurons, and neuronal apoptosis. Recently, it was found that NTE also has an important function in mammalian renal cells (22). High NaCl concentrations in the renal inner medulla induce an increase of glycerophosphocholine (GPC), an organic osmolyte and osmoprotective compatible that is derived from PC.…”
mentioning
confidence: 99%
“…High NaCl and high urea increase abundance of GPC, but by somewhat different mechanisms. High NaCl increases RNA and protein abundance of NTE, and thus its phospholipase activity, which catalyzes production of GPC from phosphatidylcholine, but high urea does not (4). Also, high NaCl decreases mRNA abundance of GDPD5 via an increase of its degradation rate, although high urea does not.…”
mentioning
confidence: 99%
“…GPC, like other compatible organic osmolytes (2), protects cells by stabilizing intracellular macromolecules against the perturbing effects of the high NaCl and urea (3). GPC is synthesized from phosphatidylcholine, catalyzed by phospholipase B activity of neuropathy target esterase (NTE) (4,5), and it is degraded to choline and glycerol-3-phosphate, catalyzed by glycerophosphocholine-phosphodiesterase (GPC-PDE) activity of the phosphodiesterase phosphodiesterase domain containing 5 (GDPD5) (6,7). High NaCl and high urea increase abundance of GPC, but by somewhat different mechanisms.…”
mentioning
confidence: 99%